Bacterial Genotyping of Central Nervous System Tuberculosis in South Africa: Heterogenic Mycobacterium tuberculosis Infection and Predominance of Lineage 4 - van Leeuwen, L M; Versteegen, P; Zaharie, S D; van Elsland, S L; Jordaan, A; Streicher, E M; Warren, R M; van der Kuip, M; van Furth, A M (Journal of clinical microbiology, 2019)
Tuberculous meningitis (TBM), the most severe extrapulmonary manifestation of tuberculosis, is caused by the pathogen The complex includes seven lineages, all described to harbor a unique geographical dissemination pattern and clinical presentation. In this study, we set out to determine whether a certain lineage demonstrated tropism to cause TBM in patients from Cape Town, South Africa. DNA was extracted from formalin-fixed paraffin-embedded central nervous system (CNS) tissue from a unique neuropathological cohort of 83 TBM patients, collected between 1975 and 2012. lineages 1, 2, 3, and 4 were determined using an allele-specific PCR and Sanger sequencing. Of the 83 patient specimens tested, bacterial characterization could be performed on 46 specimens (55%). lineage 4 was present in 26 patient specimens (56%), and non-lineage 4 was identified in 10 cases (22%). Moreover, genomic heterogeneity was detected in the CNS specimens of 7 adults and 3 children. We could show that infection of the CNS is not restricted to a single lineage and that even young children with rapid progression of disease can harbor more than one lineage in the CNS.